2020
DOI: 10.1002/cpdd.864
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Bioequivalence of 2 Immediate‐Release Tofacitinib Tablet Formulations in Chinese Healthy Volunteers Under Fasting and Fed Conditions

Abstract: The purpose of this study was to evaluate the bioequivalence of a generic immediate-release tofacitinib tablet versus a brand-named immediate-release tofacitinib tablet under fasting and fed conditions, and the food effect on pharmacokinetic profiles of the both formulations. This randomized, open-label, 2-period, crossover, bioequivalence study included 52 healthy Chinese subjects (fasting cohort: n = 26; fed cohort: n = 26). The subjects were assigned to receive a single 5-mg dose of generic or brand-named t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
2
3
1
Order By: Relevance
“…However, another study showed that a high-diet had no efect on AUC 0-t and AUC 0-∞ [14]. In our study trial, the value of t 1/2 was in average delayed 0.45 h after a high-fat diet, and it is diferent to the previous studies [12,14]; the previous study showed that there was no signifcant difference in the value of t 1/2 . But in another study [13], it was also proven that a high-fat diet can extend t 1/2 about 0.2 h. Overall, a high-fat diet can afect the pharmacokinetic behavior of tofacitinib.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…However, another study showed that a high-diet had no efect on AUC 0-t and AUC 0-∞ [14]. In our study trial, the value of t 1/2 was in average delayed 0.45 h after a high-fat diet, and it is diferent to the previous studies [12,14]; the previous study showed that there was no signifcant difference in the value of t 1/2 . But in another study [13], it was also proven that a high-fat diet can extend t 1/2 about 0.2 h. Overall, a high-fat diet can afect the pharmacokinetic behavior of tofacitinib.…”
Section: Discussioncontrasting
confidence: 95%
“…In our study trial, the values of C max and T max are similar to previous studies and food afection on exposure of tofacitinib. Te value of C max in average decreased by 25.90%, and it is similar to previous studies [12][13][14]. In our study, the value of AUC 0-t and AUC 0-∞ was in average increased by 16.57% and 14.08%, respectively, after a high-fat diet in the fasted state, which is similar to the previous study [13].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Suitable healthy Chinese subjects were included in our study. The inclusion criteria were as follows: (1) aged >18 years, both men and women; (2) male subjects weighing more than 50 kg and female subjects weighing more than 45 kg; body mass index 19–26 kg/m 2 , including the boundary value; (3) subjects provided informed consent before participating in the study; and (4) subjects were able to communicate well with the researcher and understand and comply with the requirements of the study 16,17 . The exclusion criteria are shown in Supplemental Information .…”
Section: Methodsmentioning
confidence: 99%